2000
DOI: 10.1063/1.1290728
|View full text |Cite
|
Sign up to set email alerts
|

High-performance all-polymer integrated circuits

Abstract: In this letter, we demonstrate the integration of all-polymer field-effect transistors in fully functional integrated circuits with operating frequencies of several kHz. One of the key items is an approach to incorporate low-Ohmic vertical interconnects compatible with an all-polymer approach. Inverters, NAND gates, and ring oscillators with transistor channel lengths down to 1 μm have been constructed. Inverters show voltage amplification at moderate biases and pentacene seven-stage ring oscillators show swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
245
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 462 publications
(251 citation statements)
references
References 18 publications
6
245
0
Order By: Relevance
“…However, there are still four experimental modes denoted as 1 , 2 , 3 , and 4 in Table I which are not assigned by the isolated chain model calculation. 16 To see whether those modes derive from the crystalline nature of the measured samples, we have performed calculations for crystalline PPV and have found that the four experimental frequencies are successfully reproduced in our calculation, as shown in Table II.…”
Section: A Vibrational Propertiesmentioning
confidence: 99%
“…However, there are still four experimental modes denoted as 1 , 2 , 3 , and 4 in Table I which are not assigned by the isolated chain model calculation. 16 To see whether those modes derive from the crystalline nature of the measured samples, we have performed calculations for crystalline PPV and have found that the four experimental frequencies are successfully reproduced in our calculation, as shown in Table II.…”
Section: A Vibrational Propertiesmentioning
confidence: 99%
“…The wide range of controllable optoelectronic properties, coupled with excellent stability, make them attractive as electronic materials for potential use in a variety of applications such as biosensors, 4 batteries, 5 and field effect transistors. [6][7][8] Experimental and theoretical investigations of the dynamical properties of conjugated polymers play a key role in understanding the structural and microscopic optoelectronic properties of the materials in various phases in both the pristine and doped states. 9,10 However, it is often the case that information obtained by different methods has been quite inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in organic thin-film transistors ͑TFTs͒ has grown rapidly due to envisaged applications, such as integrated circuits 1 and active-matrix displays. 2 The switching speed of organic integrated circuits can be estimated from the performance of the individual transistors and is roughly proportional to ϳ FE /L 2 , 3 where L is the channel length of the transistor, and FE is the field-effect mobility.…”
mentioning
confidence: 99%